Electrochemically exfoliated black phosphorus nanosheets - prospective field emitters - Erande, Manisha B.; Suryawanshi, Sachin R.; More, Mahendra A.; Late, Dattatray J. (European Journal of Inorganic Chemistry, 2015)
Herein we report field emission (FE) investigations on an electrochemically exfoliated few-layered black phosphorus nanosheet emitter at a base pressure of approximately 1x10(-8) mbar. The turn-on electric field required to draw an emission current density of approximately 10 A/cm(2) is found to be about 4.2 V/m. Furthermore, few-layered black phosphorus nanosheet emitters deliver an emission current density of about 170 A/cm(2) at an applied field of about 7.5 V/m. The emission current vs. time plot measured at preset current values of about 5 A shows emission current fluctuations within +/- 10% of the average value, indicating the highly stable nature of the black phosphorus field emitter. Thus, the 2D black phosphorus nanosheets synthesized using the simple electrochemical exfoliation method can be utilized for micro/nanoelectronics and flat panel FE display applications.
Keywords: field emission; Layered compounds; Nanostructures; Phosphorus

Spectral analysis of the emission current noise exhibited by few layer WS2 nanosheets emitter - Suryawanshi, Sachin R.; Kolhe, Pankaj S.; Rout, Chandra S.; Late, Dattatray J.; More, Mahendra A. (Ultramicroscopy, 2015)
Spectral analysis of the field emission (FE) current fluctuations has been carried out at the base pressure similar to 1 x 10(-8) mbar. The emission current stability investigated at preset value of 2 mu A is characterized by `step like fluctuation. The spectral analysis performed on a FFT (Fast Fourier Transform) analyzer revealed that the observed noise is of 1/f(alpha) type, with the value of alpha as similar to 1.05. The estimated value of alpha implies that the current fluctuations are mainly due the various processes occurring on atomic scale like adsorption, migration, and/or desorption of the residual gas species on the emitter surface. (C) 2014 Elsevier B.V. All rights reserved.
Keywords: Current fluctuations; field emission; Noise; WS2 nanosheets

Architecture of 2D MoS2 nanosheets and 3D CdMoS4 marigold flowers: consequence of annealing on field emission performance - Kadam, Sunil R.; Suryawanshi, Sachin R.; Panmand, Rajendra P.; Mate, Vivek R.; More, Mahendra A.; Late, Dattatray J.; Kale, Bharat B. (Microporous and Mesoporous Materials, 2016)
Herein, we report the field electron emission investigations on template free solvothermally synthesized layered MoS2 nanosheets as well as novel phase of CdMoS4 nanoflowers at the base pressure of similar to 1 x 10(-8) mbar. The turn-on field, threshold field and maximum emission current densities for both MoS2 and CdMoS4 are strongly influenced by thermal annealing in inert atmosphere. The turn on field, required to draw emission current density of 1 mu A/cm(2) is found to be 5.8 and 3.2 V/mu m for pristine and annealed MoS2 at 400 degrees C. In case of as prepared and annealed CdMoS4 sample the turn on field values are found to be similar to 6.2 and 5.0 V/mu m, respectively. The emission current versus time (I-t) plot measured at the preset current values of similar to 1 mu A for pristine and annealed sample indicates stable operation of the emitter. The emission current fluctuations for annealed sample are observed to be less as compared with the pristine sample due to conditioning of the emitter, thereby showing highly stable nature of emitter. Thus, the present result demonstrates the potential of annealed MoS2 nanosheets and CdMoS4 nanoflowers as an emerging materials for micro/nanoelectronics and flat panel field emission display applications. (C) 2016 Elsevier Inc. All rights reserved.
Keywords: field emission; MoS2 and CdMoS4; Nanoflowers; nanosheets

Enhanced field emission behavior of layered MoSe2 - Suryawanshi, Sachin R.; Pawbake, Amit S.; Pawar, Mahendra S.; Jadkar, Sandesh R.; More, Mahendra A.; Late, Dattatray J. (Materials Research Express, 2016)
Herein, we report one step facile chemical vapor deposition method for synthesis of single-layer MoSe2 nanosheets with average lateral dimension similar to 60 mu m on 300 nm SiO2/Si and n-type silicon substrates and field emission investigation of MoSe2/Si at the base pressure of similar to 1 x 10(-8) mbar. The morphological and structural analyses of the as-deposited single-layer MoSe2 nanosheets were carried out using an optical microscopy, Raman spectroscopy and atomic force microscopy. Furthermore, the values of turn-on and threshold fields required to extract an emission current densities of 1 and 10 mu A cm(-2), are found to be similar to 1.9 and similar to 2.3 V mu m(-1), respectively. Interestingly, the MoSe2 nanosheet emitter delivers maximum field emission current density of similar to 1.5 mA cm(-2) at a relatively lower applied electric field of similar to 3.9 V mu m(-1). The long term operational current stability recorded at the preset values of 35 mu A over 3 hr duration and is found to be very good. The observed results demonstrates that the layered MoSe2 nanosheet based field emitter can open up many opportunities for their potential application as an electron source in flat panel display, transmission electron microscope, and x-ray generation. Thus, the facile one step synthesis approach and robust nature of single-layer MoSe2 nanosheets emitter can provide prospects for the future development of practical electron sources.
Keywords: atomically thin nanosheets; chemical vapor deposition; field emission; layered MoSe2

Synthesis, microstructure, optical and field emission studies of iron vanadium oxide nanosheets - Badadhe, Satish S.; Suryawanshi, Sachin R.; Naphade, Rounak A.; Chaudhary, Minakshi V.; More, Mahendra A.; Shelke, Manjusha V.; Ogale, Satishchandra B. (Journal of Physics D-Applied Physics, 2016)
We report a single step growth of thin graphene-like, densely packed FeV3O8 (FVO) nanosheets on silicon substrates via facile hydrothermal synthesis. These nanosheets have dimensions of a few microns with thin edges, offering very high aspect ratio. These FVO nanosheets exhibit excellent field emission behaviour with low turn on and threshold voltages of 1.3 V mu m(-1) and 1.7 V mu m(-1), respectively. The corresponding emitter delivers high emission current density of (similar to 1.650 mA cm(-2)) at fairly low applied field (similar to 4.00 V mu m(-1)).
Keywords: FeV3O8; field emission; nanosheets

Extraction of the very high tunneling current and extremely stable emission current from GdB6/W-tip source synthesized using arc plasma - Suryawanshi, Sachin R.; Kanhe, Nilesh; Mathe, Vikas L.; Phase, Deodatta M.; Late, Dattatray J.; More, Mahendra A. (ChemistrySelect, 2017)
Herein, we report the one step arc plasma synthesis of the GdB6 (Gadolinium hexaboride) nanoparticles and its field emission (FE) characteristics on tungsten point substrate (GdB6/ W). The SEM /TEM analysis revealed the GdB6 nanoparticles on W point substrate exhibit irregular shaped, grainy, dense, course morphology, i.e. uniformly covering the entire tip substrate surface. For GdB6/W point source, the values of the turn-on and threshold fields, defined as field required to draw an emission current density similar to 1 mA/cm(2) and similar to 100 mA/cm(2), respectively are found to be similar to 2.2 and similar to 2.7 V/mm, for anodecathode separation of similar to 1 mm. Interestingly, a very high emission current density of similar to 3.5 A/cm(2) has been drawn from the GdB6/W point emitter at relatively lower applied field of similar to 6.4 V/mm. The field enhancement factor found to be similar to 10,250. The GdB6/W point electron source exhibits a good emission current stability at similar to 10 mA for a period of 6 hr. The emission current stability is enumerated in terms of standard deviation and its magnitude has been measured to be only 1.72% with respect to the average value. The superlative field emission characteristics signify the GdB6/W point electron source as potential candidates for vacuum micro/nanoelectronics device applications.
Keywords: Arc Plasma; field emission; Thin films